PERAN AKUNTAN PUBLIK DALAM PENERAPAN GOOD GOVERNANCE DI PASAR MODAL (TINJAUAN STANDAR AUDIT) - Arda, Devid Putra (Unversitas Prof. Dr. Moestopo (Beragama), 2024)
Capital markets are an important component in the global financial system that facilitates long-term fundraising through the issuance of shares and bonds. Capital market management must prioritize good governance (GC). A number of fraud cases in the capital market indicate weak implementation of GC. Public accountants play a major role in the capital market in assessing the fairness of issuers' financial statements. For this reason, it is necessary to analyze how much guidance applies professional skepticism to public accountants. This research emphasizes research on audit standards (SA) published by the Indonesian Institute of Public Accountants (IAPI) regarding professional skepticism as a guide for public accountants. There are two important SAs that emphasize professional skepticism, namely (SA) 200 (revised 2021), concerning